Studying Macromolecular Composition in Cell–Cell Interfaces Using 3D Membrane Reconstitution Systems - Sezgin, Erdinc; Ragaller, Franziska; Schneider, Amelie Maribel; Sjule, Ellen; Sun, Renhua; Han, Xiao; Andronico, Luca; Jenkins, Edward; Dustin, Michael L.; Achour, Adnane (Karolinska Institutet, 2026)
It contains data sets from the publication, with the details for citation provided in the README file.

Please cite this item as:

F. Ragaller, A. M. Schneider, E. Sjule, R. Sun, X. Han, L. Andronico, E. Jenkins, M. Dustin, A. Achour, E. Sezgin

DOI: 10.17044/scilifelab.30540932

It contains raw microscopy images, figures and excel sheets of the data.

Abstract

During direct communication between two cells, the plasma membranes of each cell serve as a platform for ligand-receptor interaction initiating downstream signalling cascades. In immune cell signalling, this cell-cell interface – the immune synapse – is highly spatiotemporally organized. Multiple stimulatory and co-stimulatory signals need to be integrated over time to ensure proper immune cell function. This process is still not fully understood given the vast complexity of interactions between proteins, lipids, glycocalyx and associated cortical actin cytoskeleton. Here, we presented a fully artificial model system to study the interface between two vesicles and a semi-artificial one between a live cell and a vesicle to reconstitute 3D contacts. We investigated the distribution and reorganization of immune cell proteins at artificial and semi-artificial contacts. We show the enrichment and depletion of different proteins in the synapse and how different peptides with varying affinity presented by the same major histocompatibility complex (MHC) class I affect T cell activation. We further explored the distribution of glycocalyx elements and showed differential partitioning of different sugar moieties in the interface. While we focused on the T cell interface here, our model systems are powerful tools to study distribution and reorganization of lipids, proteins and glycocalyx components at any cell-cell contact.

Data usage

Researchers are welcome to use the data contained in the dataset for any projects. Please cite this item upon use or when published. We encourage reuse using the same CC BY 4.0 License.

Data Content

Excel files for graphs

lsm or czi files for raw microscopy images

tif files for processed microscopy images

svg files for figures

Software to open files

.xlsx - Microsoft excel

.czi - Fiji (https://imagej.net/Fiji.html#Downloads)

.tif - Fiji (https://imagej.net/Fiji.html#Downloads)

.svg - Inkscape
Keywords: Synthetic biology; Receptors and membrane biology; Glycobiology; Cellular interactions (incl. adhesion, matrix, cell wall); Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi